Composite current collector, preparation method thereof and secondary battery

By designing composite fluid collection in lithium-ion batteries, and using the laminated structure of polymers, two-dimensional nanoribbons, binders, inorganic foaming agents and high-entropy alloy materials, the problem of thermal runaway in lithium-ion batteries at high temperatures is solved. Improves battery safety and cycle performance.

CN119297293AActive Publication Date: 2025-01-10SHENZHEN HANKE NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411828276.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-10
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to thermal runaway at high temperatures, resulting in poor safety performance. In addition, traditional composite liquid collectors cannot cut off the circuit in time when the internal short circuit of the battery cell, resulting in heat accumulation and seriously damaging battery safety.

Method used

Provided is a composite fluid, including a sequentially stacked support layer, a safety coating and a protective coating, the support layer consisting of a polymer material and a two-dimensional nanoribbon material, and the safety coating contains a binder and an inorganic foaming agent to protect it. The coating uses a high entropy alloy material, which increases the resistance by providing grooves on the surface of the support layer to increase adhesion and releases the gas to rupture the conductive layer at high temperatures.

Benefits of technology

It improves the battery's conductivity, structural stability and safety performance, reduces the probability of thermal runaway at high temperatures, and improves the battery's cycling performance under normal operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297293A_ABST
    Figure CN119297293A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a composite current collector, a preparation method thereof and a secondary battery. The composite current collector comprises a supporting layer, a safety coating, a protective coating and a conductive layer which are stacked in sequence, the supporting layer comprises a polymer material and a two-dimensional nanobelt material; the safety coating comprises a binder and an inorganic foaming agent, and the thermal decomposition temperature of the inorganic foaming agent is 80-130 DEG C; and the protective coating comprises a high-entropy alloy material. The composite current collector provided by the invention is good in conductivity, high in structural stability and excellent in safety performance, the probability of thermal runaway of the battery at a high temperature can be reduced, and the cycle performance of the battery under a normal working condition can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite current collector and a preparation method thereof, and a secondary battery. Background Art

[0002] The large-scale use of traditional fossil fuels has led to increasingly serious problems such as resource shortages and environmental pollution. It is of great significance to accelerate the transformation of energy structure and develop clean renewable energy. Among them, lithium-ion batteries, as a secondary battery, are widely used in 3C products, energy storage systems and power batteries due to their high energy density, long cycle life, good rate performance and low cost. How to further improve the energy density, cycle life and safety performance of lithium-ion batteries has also become a research hotspot in the field of lithium-ion batteries.

[0003] During the use of lithium-ion batteries, irregular growth of negative electrode lithium dendrites, shrinkage or melting of the diaphragm at high temperature, and external mechanical abuse (such as puncture, extrusion or impact) can easily cause a short circuit inside the battery cell and generate a large amount of heat, causing local temperature rise and thermal runaway, seriously damaging the safety performance of the battery. Summary of the invention

[0004] Based on this, it is necessary to provide a composite current collector and a preparation method thereof and a secondary battery to solve the problem that the battery is prone to thermal runaway at high temperatures and has poor battery safety performance.

[0005] The above-mentioned purpose of the present application is achieved through the following technical solutions:

[0006] In a first aspect of the present application, a composite current collector is provided, comprising a support layer, a safety coating, a protective coating and a conductive layer stacked in sequence;

[0007] The support layer includes a polymer material and a two-dimensional nanobelt material;

[0008] The safety coating comprises a binder and an inorganic foaming agent, and the thermal decomposition temperature of the inorganic foaming agent is 80° C. to 130° C.;

[0009] The protective coating includes a high entropy alloy material.

[0010] In some embodiments, a plurality of grooves are provided on the surface of the support layer, and the depth of the grooves is less than the thickness of the safety coating;

[0011] The safety coating is filled in the groove;

[0012] The protective coating covers the safety coating and the supporting layer.

[0013] In some embodiments, the depth of the groove is 0.1 μm to 1 μm, the size of the groove is 1 μm to 2 μm, and the spacing between the grooves is 200 μm to 1000 μm.

[0014] In some embodiments, the polymer material includes one or more of polyethylene, polypropylene, polyimide, polyvinyl chloride, polystyrene, polyvinyl alcohol, polyethylene terephthalate, and polybutylene terephthalate.

[0015] In some embodiments, the two-dimensional nanoribbon material includes one or more of tantalum arsenide nanoribbons, niobium arsenide nanoribbons, tantalum phosphide nanoribbons, and niobium phosphide nanoribbons.

[0016] In some embodiments, the two-dimensional nanobelt material has a thickness of 50 nm to 400 nm, a width of 100 nm to 500 nm, and a length of 0.1 mm to 1 mm.

[0017] In some embodiments, the mass ratio of the polymer material to the two-dimensional nanobelt material is 100:(1-30).

[0018] In some embodiments, the thickness of the support layer is 4 μm to 8 μm.

[0019] In some embodiments, the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium alginate, polyvinyl alcohol, polymethyl methacrylate, hydrogenated nitrile rubber, and polyacrylic acid.

[0020] In some embodiments, the inorganic blowing agent includes one or more of carbonates, bicarbonates, and hydrated silicates.

[0021] In some embodiments, the mass ratio of the binder to the inorganic foaming agent is 1:(2-3).

[0022] In some embodiments, the safety coating has a thickness of 0.2 μm to 2 μm.

[0023] In some embodiments, the high entropy alloy material includes at least five of iron, cobalt, nickel, chromium, manganese, aluminum, copper, titanium, yttrium, and tantalum.

[0024] In some embodiments, the protective coating has a thickness of 20 nm to 50 nm.

[0025] In some embodiments, the material of the conductive layer includes one or more of stainless steel, copper, nickel, and aluminum.

[0026] In some embodiments, the thickness of the conductive layer is 0.5 μm to 4 μm.

[0027] In a second aspect of the present application, a method for preparing the composite current collector as described above is provided, comprising the following steps:

[0028] The polymer material and the two-dimensional nanobelt material are melt-blended and molded to form a support layer;

[0029] A safety coating layer, a protective coating layer and a conductive layer are sequentially formed on the support layer.

[0030] In some embodiments, the method for preparing the safety coating comprises the following steps:

[0031] Covering the support layer with a mixed slurry containing a binder and an inorganic foaming agent, and drying the mixed slurry to obtain the safety coating; or,

[0032] The surface of the support layer includes a first area and a second area arranged around the first area;

[0033] forming a plurality of grooves on the first region and covering the second region with a mask;

[0034] The groove is filled with a mixed slurry containing a binder and an inorganic foaming agent, and then dried, and the mask is removed to obtain the safety coating.

[0035] In a second aspect of the present application, a secondary battery is provided, comprising the composite current collector as described above, or comprising a composite current collector made by the method for preparing the composite current collector as described above.

[0036] This application has at least the following beneficial effects:

[0037] The composite current collector provided by the present application includes a support layer, a safety coating, a protective coating and a conductive layer stacked in sequence. Among them, the support layer is composited by a polymer material and a two-dimensional nanobelt material, which can enhance the tensile strength, elongation at break and toughness of the support layer, and improve the mechanical properties of the composite current collector; at the same time, the two-dimensional nanobelt material has excellent electronic conductivity, which can enhance the conductivity of the support layer, thereby improving the overcurrent heating problem caused during high-rate operation, and ensuring the stable performance of the battery's electrochemical performance. The safety coating is composited by a binder and an inorganic foaming agent. The thermal decomposition temperature of the inorganic foaming agent is 80°C~130°C. The inorganic foaming agent absorbs heat at high temperatures and undergoes thermal decomposition, and releases a large amount of gas, which exerts a strong impact on the protective coating and the conductive layer, causing the conductive layer to rupture and peel off, thereby increasing the resistance impedance of the composite current collector, suppressing abnormal loop current, and effectively improving the safety performance of the battery. The protective coating is made of high entropy alloy material, which has excellent fracture resistance, tensile strength, corrosion resistance, oxidation resistance and bonding performance, can protect the support layer and the safety coating, so that the inorganic foaming agent in the safety coating can be stably stored, and at the same time, it can also enhance the bonding force between the layers, thereby improving the structural stability of the composite current collector. Therefore, the composite current collector provided by the present application has good electrical conductivity, high structural stability and excellent safety performance, which can not only reduce the probability of thermal runaway of the battery at high temperature, but also help to improve the cycle performance of the battery under normal operating conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0039] Figure 1 Schematic diagram of the structure of a composite current collector in one embodiment of the present application;

[0040] Figure 2 is a schematic structural diagram of a composite current collector in another embodiment of the present application;

[0041] Figure 3 is a cross-sectional schematic diagram of a support layer in one embodiment of the present application;

[0042] Figure 4 Schematic diagram of a process for preparing a composite current collector in one embodiment of the present application;

[0043] Figure 5 Schematic diagram of a process for preparing a safety coating in one embodiment of the present application.

[0044] Reference numerals: support layer 10 , groove 11 , safety coating 20 , protective coating 30 , conductive layer 40 . DETAILED DESCRIPTION

[0045] In order to facilitate the understanding of the present application, the present application is further described in detail below in conjunction with specific embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0047] In the present application, the meaning of "and / or" includes any and all combinations of one or more related listed items. "At least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layer" means at least two layers, such as two layers, three layers, etc., unless otherwise clearly and specifically defined. In the description of the present application, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0048] When a numerical range is disclosed in this application, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed in this application should be understood to include any and all subranges included therein.

[0049] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0050] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.

[0051] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0052] In the present application, room temperature refers to indoor temperature, normal temperature or general temperature. Generally speaking, the range of room temperature can be any one of the following temperature intervals: 23°C ± 2°C, 25°C ± 5°C or 20°C ± 5°C.

[0053] Current collectors can be divided into two categories: metal current collectors and composite current collectors. Composite current collectors are usually composed of a polymer layer and a metal layer covering at least one side of the polymer layer. Compared with metal current collectors such as copper foil and aluminum foil, composite current collectors are lighter, thinner and have better safety performance. However, traditional composite current collectors cannot cut off the circuit in time when a short circuit occurs inside the battery cell, which can easily lead to heat accumulation and thermal runaway, and the safety performance needs to be further improved.

[0054] Based on this, in the first aspect of the present application, a composite current collector is provided to reduce the probability of thermal runaway of the battery at high temperatures and improve the safety performance of the battery.

[0055] See also Figure 1 , which is a schematic diagram of the structure of a composite current collector in one embodiment of the present application.

[0056] like Figure 1 As shown, the composite current collector includes a support layer 10, a safety coating 20, a protective coating 30 and a conductive layer 40 stacked in sequence;

[0057] The support layer 10 includes a polymer material and a two-dimensional nanobelt material;

[0058] The safety coating 20 includes a binder and an inorganic foaming agent, and the thermal decomposition temperature of the inorganic foaming agent is 80° C. to 130° C.;

[0059] The protective coating 30 includes a high entropy alloy material.

[0060] The composite current collector provided by the present application includes a support layer 10, a safety coating 20, a protective coating 30 and a conductive layer 40 stacked in sequence. Among them, the support layer 10 is composed of a polymer material and a two-dimensional nanobelt material, which can enhance the tensile strength, elongation at break and toughness of the support layer 10 and improve the mechanical properties of the composite current collector; at the same time, the two-dimensional nanobelt material has excellent electronic conductivity, which can improve the conductivity of the support layer 10, thereby improving the overcurrent heating problem caused during high-rate operation and ensuring the stable performance of the battery's electrochemical performance. The safety coating 20 is composed of a binder and an inorganic foaming agent. The thermal decomposition temperature of the inorganic foaming agent is 80°C~130°C. The inorganic foaming agent absorbs heat at high temperatures and undergoes thermal decomposition, and releases a large amount of gas, which produces a strong impact on the protective coating 30 and the conductive layer 40, causing the conductive layer 40 to rupture and peel off, thereby increasing the resistance impedance of the composite current collector, suppressing abnormal loop current, and effectively improving the safety performance of the battery. The protective coating 30 is made of a high entropy alloy material, which has excellent fracture resistance, tensile strength, corrosion resistance, oxidation resistance and bonding performance, and can protect the support layer 10 and the safety coating 20, so that the inorganic foaming agent in the safety coating 20 can be stably stored, and at the same time, the bonding force between the layers can be enhanced, thereby improving the structural stability of the composite current collector. Therefore, the composite current collector provided by the present application has good electrical conductivity, high structural stability and excellent safety performance, which can not only reduce the probability of thermal runaway of the battery at high temperature, but also help to improve the cycle performance of the battery under normal operating conditions.

[0061] Optionally, the polymer material includes one or more of polyethylene (PE), polypropylene (PP), polyimide (PI), polyvinyl chloride (PVC), polystyrene (PS), polyvinyl alcohol (PVA), polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), and may further be one or more of polypropylene (PP), polyimide (PI) and polyethylene terephthalate (PET).

[0062] Optionally, the two-dimensional nanobelt material includes one or more of tantalum arsenide (TaAs) nanobelt, niobium arsenide (NbAs) nanobelt, tantalum phosphide (TaP) nanobelt and niobium phosphide (NbP) nanobelt, and may further be NbAs nanobelt.

[0063] Two-dimensional nanobelt materials refer to ribbon materials with nanometer-level width in a two-dimensional plane, and their length can reach micrometer level or even millimeter level, and their width and thickness are generally between a few nanometers and a few hundred nanometers, showing typical two-dimensional characteristics, and can give the support layer 10 better conductivity and mechanical strength. Among them, TaAs, NbAs, TaP and NbP are Weyl semimetal materials, with topologically protected conductive states on the surface, high carrier mobility, and linearly dispersed energy band structures, thus showing excellent conductive properties.

[0064] Optionally, the two-dimensional nanobelt material has a thickness of 50nm~400nm, a width of 100nm~500nm, and a length of 0.1mm~1mm. As an example, the thickness of the two-dimensional nanobelt material includes but is not limited to 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm or 400nm; the width of the two-dimensional nanobelt material includes but is not limited to 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm or 500nm; the length of the two-dimensional nanobelt material includes but is not limited to 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm or 1mm.

[0065] Optionally, the mass ratio of the polymer material to the two-dimensional nanobelt material is 100:(1-30). As an example, the mass ratio of the polymer material to the two-dimensional nanobelt material includes but is not limited to 100:1, 100:2, 100:4, 100:6, 100:8, 100:10, 100:12, 100:14, 100:16, 100:18, 100:20, 100:22, 100:24, 100:26, 100:28, 100:30, and may further be 100:(5-15).

[0066] Adding an appropriate amount of two-dimensional nanobelt material to the support layer 10 can give full play to its toughening effect, enabling it to play a role in buffering stress and maintaining structural stability during the preparation and operation of the battery cell. At the same time, it can also build a complete conductive network in the support layer 10 to improve the heat generation problem caused by large current transportation, thereby providing a guarantee for the stable performance of the battery performance.

[0067] Optionally, the thickness of the support layer 10 is 4 μm to 8 μm. As an example, the thickness of the support layer 10 includes but is not limited to 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm or 8 μm.

[0068] Optionally, the binder includes one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR) and polyacrylic acid (PAA), and may further be polyvinylidene fluoride (PVDF).

[0069] Optionally, the inorganic foaming agent includes one or more of carbonate, bicarbonate and hydrated silicate. Further optionally, the inorganic foaming agent includes beryllium carbonate (BeCO 3 ), sodium bicarbonate (NaHCO 3 )、Potassium bicarbonate (KHCO 3 ), cesium bicarbonate (CsHCO 3 ) and sodium silicate decahydrate (Na 2 SiO 3 10H 2 O), and further can be beryllium carbonate (BeCO 3 ) or sodium silicate decahydrate (Na 2 SiO 3 10H 2 O).

[0070] BeCO 3 The thermal decomposition temperature of NaHCO is ~100 °C. 3 The thermal decomposition temperature of KHCO is 100℃~120℃. 3 It starts to decompose at around 100°C, CsHCO 3 It starts to decompose at around 100°C. 2 SiO 3 10H 2 O starts to lose crystal water at around 100°C. The above carbonates, bicarbonates and hydrated silicates as inorganic foaming agents can absorb heat and decompose to form CO under conditions higher than the thermal decomposition temperature. 2 , H 2 O and other non-flammable gases, no formation of NH 4 Combustion-supporting gases such as chlorinated carbon monoxide and chlorinated carbon can help isolate oxygen and achieve flame retardant and explosion-proof effects.

[0071] Optionally, the mass ratio of the binder to the inorganic foaming agent is 1:(2-3). As an example, the mass ratio of the binder to the inorganic foaming agent includes but is not limited to 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 or 1:3.

[0072] Optionally, the thickness of the safety coating 20 is 0.2 μm to 2 μm. As an example, the thickness of the safety coating 20 includes but is not limited to 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm or 2 μm.

[0073] Optionally, the high entropy alloy material includes at least five of iron (Fe), cobalt (Co), nickel (Ni), chromium (Cr), manganese (Mn), aluminum (Al), copper (Cu), titanium (Ti), yttrium (Y) and tantalum (Ta), and can be further selected as at least five of nickel (Ni), cobalt (Co), chromium (Cr), aluminum (Al), yttrium (Y) and tantalum (Ta). Further optionally, the high entropy alloy material is NiCoCrAlY or NiCoCrAlYTa.

[0074] High-entropy alloys (HEA) are alloy materials composed of at least five metals transported in an equiatomic ratio or a nearly equiatomic ratio. Unlike traditional alloys with one or two metal elements as the dominant components, multiple metal elements in HEA materials jointly occupy a dominant position, and the mixing entropy is relatively high. They usually present a simple crystal structure (such as face-centered cubic structure, body-centered cubic structure or close-packed hexagonal structure) and have microstructural uniformity, so they show excellent fracture resistance, tensile strength, corrosion resistance and oxidation resistance, so that the protective coating 30 plays a good protective role on the support layer 10 and the safety coating 20. Its excellent bonding performance is also conducive to enhancing the bonding strength between the safety coating 20 and the conductive layer 40, and preventing the safety coating 20 from falling off, peeling off, decomposing, etc. before it takes effect.

[0075] Optionally, the thickness of the protective coating 30 is 20 nm to 50 nm. As an example, the thickness of the protective coating 30 includes, but is not limited to, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.

[0076] Optionally, the material of the conductive layer 40 includes one or more of stainless steel, copper (Cu), nickel (Ni) and aluminum (Al), and may further be copper (Cu) or aluminum (Al).

[0077] Optionally, the thickness of the conductive layer 40 is 0.5 μm to 4 μm. As an example, the thickness of the conductive layer 40 includes but is not limited to 0.5 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2 μm, 2.2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.2 μm, 3.5 μm, 3.8 μm or 4 μm.

[0078] See also Figure 2 , which is a schematic diagram of the structure of a composite current collector in another embodiment of the present application.

[0079] like Figure 2 As shown, the surface of the support layer 10 is provided with a plurality of grooves 11, and the depth of the grooves 11 is less than the thickness of the safety coating 20;

[0080] The safety coating 20 is filled in the groove 11;

[0081] The protective coating 30 covers the safety coating 20 and the support layer 10 .

[0082] In a conventional composite current collector, the surface of the polymer layer is usually roughened to increase the surface roughness in order to improve the bonding force between the polymer layer and the metal layer. In the embodiment of the present application, a plurality of grooves 11 are arranged on the surface of the support layer 10, and the safety coating 20 is filled in the grooves 11. Since the depth of the grooves 11 is less than the thickness of the safety coating 20, the safety coating 20 protrudes from the surface of the support layer 10. On the one hand, the grooves increase the contact area between the safety coating 20 and the support layer 10, thereby improving the adhesion between the two. On the other hand, the surface roughness of the combination formed by the support layer 10 and the safety coating 20 is also improved, thereby improving the adhesion between the combination and the protective coating 30 and the conductive layer 40. Therefore, the peeling strength of the entire composite current collector is high and the structural stability is good, thereby improving the cycle stability of the battery. In addition, the safety coating 20 is filled in the grooves 11. When the temperature inside the battery cell abnormally rises to the thermal decomposition temperature of the inorganic foaming agent, the inorganic foaming agent can generate a stronger impact force when it is thermally decomposed in a limited space, thereby causing the conductive layer 40 to tear or peel more quickly, and the safety performance is further improved.

[0083] Optionally, the depth of the groove 11 is 0.1 μm-1 μm, the size of the groove 11 is 1 μm-2 μm, and the interval between the grooves 11 is 200 μm-1000 μm.

[0084] It can be understood that the depth of the groove 11 refers to the size of the groove 11 in the thickness direction, the size of the groove 11 refers to the size of the groove 11 in the horizontal direction, and the spacing of the grooves 11 refers to the shortest distance between the edges of two adjacent grooves 11. As examples, the depth of the groove 11 includes but is not limited to 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm or 1μm; the size of the groove 11 includes but is not limited to 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm or 2μm; the spacing of the groove 11 includes but is not limited to 200μm, 250μm, 300μm, 350μm, 400μm, 450μm, 500μm, 550μm, 600μm, 650μm, 700μm, 750μm, 800μm, 850μm, 900μm, 950μm or 1000μm.

[0085] See also Figure 3 , which is a cross-sectional schematic diagram of the support layer 10 in one embodiment of the present application.

[0086] Optionally, the cross-sectional shape of the groove 11 in the thickness direction includes one or more of a square, a rectangle, a regular trapezoid, an inverted trapezoid, an inverted triangle, a semicircle and an irregular shape.

[0087] Optionally, the shape of the groove 11 in the direction perpendicular to the thickness includes one or more of a circle, a square, a rhombus, an equilateral triangle and an irregular shape.

[0088] In a second aspect of the present application, a method for preparing the composite current collector as described above is provided.

[0089] See also Figure 4 , which is a schematic diagram of a process for preparing a composite current collector in an embodiment of the present application. Figure 4 As shown, the preparation method of the composite current collector comprises the following steps:

[0090] S100: melt-blending and molding the polymer material and the two-dimensional nanobelt material to form a support layer 10;

[0091] S200 : forming a safety coating 20 , a protective coating 30 and a conductive layer 40 in sequence on the support layer 10 .

[0092] Optionally, the conditions of the melt blending process include: a temperature of 180°C to 450°C and a time of 0.5h to 8h. The temperature of the melt blending process includes, but is not limited to, 180°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C or 450°C; the time of the melt blending process may be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h or 8h.

[0093] Optionally, the molding process includes one or more of compression molding, hot press molding, autoclave molding and calendering molding.

[0094] Optionally, the two-dimensional nanobelt material is prepared by chemical vapor deposition (CVD).

[0095] Optionally, the method for preparing NbAs nanobelts comprises the following steps: 3 The precursors are placed in a crucible and heated to 200 °C to make NbCl 3 The particles were gasified and heated to 500 °C to gasify the As blocks; Ar and H in a volume ratio of 95:5 were used. 2 The mixed gas is used as the carrier gas to deliver the vaporized precursor into the center of the tube furnace; Si is used as the substrate, and a thin layer of SiO is deposited on the surface of the Si substrate. 2 layer, and pre-in SiO 2 A 15 nm thick Au layer is plated on the surface of the layer as a catalyst, and the substrate is placed in a tube furnace for chemical vapor deposition to react and generate NbAs nanobelts on the substrate. The conditions for chemical vapor deposition are: the temperature of the tube furnace is raised to 840°C~870°C within 15 minutes, reacted for 15 minutes, cooled to 700°C within 30 minutes, and then naturally cooled to room temperature. After the chemical vapor deposition is completed, the NbAs nanobelts are peeled off from the substrate by laser etching, plasma etching, chemical etching or mechanical stripping, such as using NH 4 Solution F etches away SiO 2 layer, thereby removing the Si substrate.

[0096] Optionally, the method for preparing the safety coating 20 comprises the following steps:

[0097] S210: Cover the support layer 10 with a mixed slurry containing a binder and an inorganic foaming agent, and dry it to obtain a safety coating 20.

[0098] See also Figure 5 , which is a schematic flow chart of a method for preparing a safety coating 20 in one embodiment of the present application. Figure 5As shown, the method for preparing the safety coating 20 comprises the following steps:

[0099] S221: The surface of the supporting layer 10 includes a first area and a second area arranged around the first area;

[0100] S222: forming a plurality of grooves 11 on the first area, and covering the second area with a mask;

[0101] S223: Fill the groove 11 with a mixed slurry containing a binder and an inorganic foaming agent, dry it, and remove the mask to obtain a safety coating 20.

[0102] Optionally, the method of forming the plurality of grooves 11 on the first region includes one or more of a laser etching method and a die cutting method.

[0103] Optionally, the mask is provided with a plurality of through holes, each of which corresponds to the groove 11 on the support layer 10, so as to fill the mixed slurry into the groove.

[0104] Optionally, the mixed slurry includes an organic solvent, and the mass ratio of the binder to the organic solvent is 1:(4-20). As an example, the mass ratio of the binder to the organic solvent includes but is not limited to 1:4, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18 or 1:20.

[0105] Optionally, the organic solvent includes one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0106] Optionally, the method of covering the mixed slurry on the support layer 10, and the method of filling the mixed liquid into the groove, each independently includes one or more of spraying, spin coating, brushing, dripping, scraping, dipping, screen printing and inkjet printing, and scraping can be further selected.

[0107] Optionally, the drying temperature is 50°C to 80°C, and the drying time is 24h to 96h. As an example, the drying temperature includes but is not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, and the drying time includes but is not limited to 24h, 36h, 48h, 60h, 72h, 84h or 96h.

[0108] Optionally, the preparation method of the protective coating 30 includes magnetron sputtering.

[0109] Optionally, the conditions for preparing the protective coating 30 by magnetron sputtering include: the sputtering atmosphere is an inert gas, the sputtering pressure is 0.1Pa~1Pa, and the sputtering power is 20W~50W. The sputtering atmosphere includes one or more of helium, neon, argon, krypton and xenon; the sputtering pressure includes but is not limited to 0.1Pa, 0.2Pa, 0.3Pa, 0.4Pa, 0.5Pa, 0.6Pa, 0.7Pa, 0.8Pa, 0.9Pa or 1Pa; the sputtering power includes but is not limited to 20W, 25W, 30W, 35W, 40W, 45W or 50W.

[0110] Optionally, the protective coating 30 is prepared by magnetron sputtering, comprising the following steps: after forming the safety coating 20, the reaction chamber is evacuated to 1×10 -5 Pa~6×10 -5 Pa, argon gas is introduced at a flow rate of 10sccm~100sccm, high entropy alloy material is used as sputtering target, and DC magnetron sputtering coating is performed under the conditions of sputtering gas pressure of 0.1Pa~1Pa and sputtering power of 20W~50W to form a protective coating 30 on the safety coating 20 (or on the safety coating 20 and the support layer 10).

[0111] Optionally, the preparation method of the conductive layer 40 includes magnetron sputtering.

[0112] Optionally, the conditions for preparing the conductive layer 40 by magnetron sputtering include: the sputtering atmosphere is an inert gas, the sputtering pressure is 0.5Pa~5Pa, and the sputtering power is 100W~200W. The sputtering atmosphere includes one or more of helium, neon, argon, krypton and xenon; the sputtering pressure includes but is not limited to 0.5Pa, 1Pa, 1.5Pa, 2Pa, 2.5Pa, 3Pa, 3.5Pa, 4Pa, 4.5Pa or 5Pa; the sputtering power includes but is not limited to 100W, 120W, 140W, 160W, 180W or 200W.

[0113] Optionally, the conductive layer 40 is prepared by magnetron sputtering, comprising the following steps: after forming the protective coating 30, the reaction chamber is evacuated to a vacuum of 1×10 -5 Pa~6×10 -5 Pa, argon gas is introduced at a flow rate of 50sccm~100sccm, a conductive metal material is used as a sputtering target, and DC magnetron sputtering coating is performed under the conditions of a sputtering gas pressure of 0.5Pa~5Pa and a sputtering power of 100W~200W to form a conductive layer 40 on the protective coating 30.

[0114] In a third aspect of the present application, a secondary battery is provided, comprising the composite current collector as described above, or comprising a composite current collector made by the method for preparing the composite current collector as described above.

[0115] It can be understood that a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as Li + 、Na + , K + ) is inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The diaphragm is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0116] Optionally, the positive electrode sheet and / or the negative electrode sheet comprises a composite current collector as described above.

[0117] Optionally, the positive electrode plate includes the composite current collector as described above and a positive electrode active layer covering at least one surface of the composite current collector; wherein the conductive layer 40 in the composite current collector is made of aluminum.

[0118] Optionally, the positive electrode active layer comprises a positive electrode active material, a conductive agent and a binder, wherein the mass ratio of the positive electrode active material, the conductive agent and the binder is (80-95):(2.5-10):(2.5-10), and further optionally 80:10:10.

[0119] Optionally, when the secondary battery is a lithium battery, the positive electrode active material includes one or more of a lithium transition metal oxide and an olivine structured lithium phosphate. Among them, the lithium transition metal oxide includes but is not limited to: lithium cobalt oxide, such as LiCoO 2 ; Lithium nickel oxide, such as LiNiO 2 ; Lithium manganese oxide, such as LiMnO 2 or LiMn 2 O 4 ; Lithium nickel cobalt oxide; Lithium manganese cobalt oxide; Lithium nickel manganese oxide; Lithium nickel cobalt manganese oxide, such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523), LiNi 0.6 Co 0.1 Mn 0.3 O 2 (NCM613), LiNi 0.6 Co0.2 Mn 0.2 O 2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811); lithium nickel cobalt aluminum oxide, such as LiNi 0.8 Co 0.15 Al 0.05 O 2 ; and modified compounds of the above lithium transition metal oxides. Lithium phosphates containing olivine structures include but are not limited to: lithium iron phosphate, such as LiFePO 4 (LFP); composite material of lithium iron phosphate and carbon; lithium manganese phosphate, such as LiMnPO 4 ; Composite materials of lithium manganese phosphate and carbon; lithium manganese iron phosphate, such as LiFe 0.5 Mn 0.5 PO 4 ; A composite material of lithium manganese iron phosphate and carbon; and a modified compound of the above-mentioned olivine structured lithium phosphate. The modified compound of each material can be one or more of doping modification and surface coating modification.

[0120] Optionally, when the secondary battery is a sodium battery, the positive electrode active material includes one or more of a transition metal oxide material, a polyanion compound material, a Prussian blue compound, and an organic positive electrode material. Among them, the transition metal oxide mainly includes a layered structure and a tunnel structure, and the structural formula can be expressed as Na x TMO 2 (TM = Co, Cu, Ni, Fe, Mn, etc.), such as NaMnO 2 、NaNiO 2 、NaCrO 2 or NaCu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 O 2 ; Polyanion compound materials include Na 3 V 2 (PO 4 ) 3 (NVP), Na 3 V 2 (PO 4 ) 2 F 3 (NVPF) and Na 2 MP 2 O 7 (M = Fe, Co, Mn or Cu), etc.; the general molecular formula of Prussian blue compounds is KM II Fe III(CN) 6 (M = Mn, Fe, Co, Ni, Zn, etc.); organic cathode materials include disodium rose palmitate (Na 2 C 6 O 6 ), perylenetetracarboxylic dianhydride (PTCDA) and perylene diimide (PTCDI). And the modified compounds of the above transition metal oxide materials, polyanion compound materials, Prussian blue compounds and organic positive electrode materials, the modified compounds of each material can be one or more of doping modification and surface coating modification.

[0121] Optionally, when the secondary battery is a potassium battery, the positive electrode active material includes one or more of a transition metal oxide material, a polyanion compound material, a Prussian blue compound, and an organic positive electrode material. Among them, the transition metal oxide mainly includes a layered structure, such as K x CrO 2 (x=0.69, 0.8, 1), K x MnO 2 (x=0.3, 0.5, 0.7), K x CoO 2 (x=0.44, 0.6), K 0.48 Mn 0.4 Co 0.6 O 2 , K x Fe0.5Mn 0.5 O 2 (x=0.45, 0.65, 0.7), K 0.45 Mn 0.5 Co 0.5 O 2 , K 0.5 Mn 0.8 Co 0.1 Ni 0.1 O 2 , K 0.67 Ni 0.17 Co 0.17 Mn 0.66 O 2 , K 1.39 Mn 3 O 6 , K 2 V 3 O 8 , K 0.72 Li 0.27 Ni 0.6 Co 0.2 Mn 0.2 O 2 , K 0.7 Fe 0.05 Co 0.1 Mn0.75 Ni 0.05 V 0.05 O 2 ; Polyanion compound materials include KFeSO 4 F, KCuSO 4 F, KVPO 4 F, KVOPO 4 , K 3 V 2 (PO 4 ) 3 etc.; the molecular formula of Prussian blue compounds is K x M[M′(CN) 6 ] 1-y (0≤x≤2, 0≤y<1,), M and M′ are transition metals such as Zn, Cu, Ni, Co, Fe, Cr, and Ti; organic cathode materials include 1,4-benzoquinone polymer (PAQS), polytriphenylamine (PTPAn), copper tetracyanoquinodimethane (CuTCNQ) and anthraquinone-2,6-disulfonate sodium (AQDs), etc. And the modified compounds of the above transition metal oxide materials, polyanion compound materials, Prussian blue compounds and organic cathode materials, the modified compounds of each material can be one or more of doping modification and surface coating modification.

[0122] Optionally, the binder in the positive electrode active layer includes one or more of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA), and can further be polyvinylidene fluoride (PVDF).

[0123] Optionally, the conductive agent in the positive electrode active layer includes one or more of conductive carbon black, super conductive carbon black, acetylene black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers, and further may be conductive carbon black (Super-P, SP).

[0124] Optionally, the preparation method of the positive electrode sheet includes the following steps: dispersing the positive electrode active material, the conductive agent and the binder in a solvent (such as N-methylpyrrolidone) to prepare a positive electrode slurry; covering the positive electrode slurry on at least one surface of the composite current collector, and obtaining the positive electrode sheet through drying, rolling and cutting.

[0125] Optionally, the negative electrode plate includes the composite current collector as described above and a negative electrode active layer covering at least one surface of the composite current collector; wherein the conductive layer 40 in the composite current collector is made of one or more of stainless steel, copper and nickel.

[0126] Optionally, the negative electrode active layer comprises a negative electrode active material, a conductive agent and a binder, wherein the mass ratio of the positive electrode active material, the conductive agent and the binder is (80-95):(2.5-10):(2.5-10), and further optionally 80:10:10.

[0127] Optionally, the negative electrode active material includes one or more of carbon-based materials, silicon-based materials, tin-based materials and lithium titanate. Among them, the carbon-based material includes one or more of artificial graphite, natural graphite, graphene, soft carbon and hard carbon; the silicon-based material includes one or more of elemental silicon, silicon oxide compound, silicon carbon composite, silicon nitrogen composite and silicon alloy; the tin-based material includes one or more of elemental tin, tin oxide compound and tin alloy.

[0128] Optionally, the binder in the negative electrode active layer includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), sodium carboxymethyl cellulose (CMC) and carboxymethyl chitosan (CMCS).

[0129] Optionally, the conductive agent in the negative electrode active layer includes one or more of conductive carbon black, superconductive carbon black, acetylene black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers, and further may be conductive carbon black (Super-P, SP).

[0130] Optionally, the preparation method of the negative electrode sheet includes the following steps: dispersing the negative electrode active material, the conductive agent and the binder in a solvent (such as deionized water) to prepare a negative electrode slurry; covering the negative electrode slurry on at least one surface of the composite current collector, and obtaining the negative electrode sheet through drying, rolling and cutting.

[0131] It can be understood that the electrolyte in the secondary battery can be liquid, gel or all-solid. Optionally, the electrolyte adopts an electrolyte solution, which includes an alkali metal salt and an organic solvent. Among them, the alkali metal salt includes lithium salt, sodium salt and potassium salt; lithium salt includes lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate. One or more; sodium salt includes sodium hexafluorophosphate, sodium bisfluorosulfonyl imide, sodium bistrifluoromethanesulfonyl imide; potassium salt includes potassium hexafluorophosphate, potassium bisfluorosulfonyl imide, bistrifluoromethanesulfonyl imide, Potassium imide; the organic solvent includes one or more of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, trimethyl phosphate, triethyl phosphate, cyclopentane, dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone and diethylene glycol dimethyl ether.

[0132] It is understandable that the separator in the secondary battery can be a porous separator with good chemical stability and mechanical stability; at the same time, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without special restrictions. Optionally, the material of the separator includes one or more of glass fiber, non-woven fabric, polyethylene (PE) and polypropylene (PP).

[0133] Optionally, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly through a winding process or a lamination process, and then injected with an electrolyte to form a battery.

[0134] Optionally, the secondary battery may include an outer package for encapsulating the electrode assembly and the electrolyte. The outer package of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be an aluminum-plastic film, etc.

[0135] It can be understood that the present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape.

[0136] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0137] Example 1

[0138] Please refer to Table 1 and Table 2. The preparation method of the secondary battery provided in this embodiment is as follows:

[0139] (1) Preparation of positive electrode sheet:

[0140] (1.1) Preparation of support layer 10:

[0141] The polymer material and the two-dimensional nanobelt material were melt-blended at 300° C., uniformly dispersed at a rotation speed of 1000 rpm for 4 hours, and formed into a support layer 10 by a calendering method.

[0142] Wherein, the polymer material is polyethylene terephthalate (PET);

[0143] The 2D nanobelt material is NbAs, with a thickness of 250 nm, a width of 400 nm, and a length of 0.5 mm;

[0144] The mass ratio of polymer material to two-dimensional nanobelt material is 100:12;

[0145] The thickness of the support layer 10 is 6 μm.

[0146] (1.2) Preparation of safety coating 20:

[0147] The surface of the support layer 10 is divided into a first area and a second area arranged around the first area. A plurality of grooves 11 are formed on the first area by laser etching, and a mask 14 is covered on the second area, and the mask 14 is provided with a plurality of through holes corresponding to the grooves 11. The binder and the inorganic foaming agent are dissolved in an organic solvent to obtain a mixed solution. The mixed solution is filled into the grooves 11 by a scraping method, dried at 60°C for 48 hours, and the mask 14 is removed to obtain a safety coating 20.

[0148] The cross-sectional shape of the groove 11 in the thickness direction is an inverted trapezoid, with a depth of 0.5µm, a short side dimension of the inverted trapezoid of 1µm, a long side dimension of the inverted trapezoid of 2µm, and a spacing of 800µm;

[0149] The binder is polyvinylidene fluoride (PVDF), and the inorganic foaming agent is sodium silicate decahydrate (Na 2 SiO 3 10H 2 O), the organic solvent is N-methylpyrrolidone (NMP), the mass ratio is 1:3:6;

[0150] The thickness of the safety coating 20 is 1.5 μm, that is, the thickness of the safety coating 20 filled in the groove 11 is 0.5 μm, and the thickness of the safety coating 20 protruding from the support layer 10 is 1 μm.

[0151] (1.3) Preparation of protective coating 30:

[0152] The reaction chamber was evacuated to 5 × 10 -5 Pa, argon gas is introduced at a flow rate of 20 sccm, high entropy alloy material is used as a sputtering target, and DC magnetron sputtering coating is performed under the conditions of sputtering gas pressure of 0.1 Pa and sputtering power of 40 W to form a protective coating 30 on the support layer 10 and the safety coating 20.

[0153] The high entropy alloy material is NiCoCrAlY, and the thickness of the protective coating 30 is 30 nm.

[0154] (1.4) Preparing the conductive layer 40:

[0155] The reaction chamber was evacuated to 5 × 10 -5 Pa, argon gas is introduced at a flow rate of 80 sccm, a conductive metal material is used as a sputtering target, and DC magnetron sputtering coating is performed under the conditions of a sputtering gas pressure of 2Pa and a sputtering power of 150W to form a conductive layer 40 on the protective coating 30.

[0156] The conductive metal material is Al, and the thickness of the conductive layer 40 is 1 μm.

[0157] (1.5) Preparation of positive electrode sheet:

[0158] The positive electrode active material NCM811, the binder PVDF, and the conductive agent SP are dispersed in the solvent NMP according to a mass ratio of 80:10:10, and the positive electrode slurry is obtained after homogenization; the positive electrode slurry is coated on the conductive layer 40 of the composite current collector P1, and the positive electrode sheet is obtained after drying, rolling and cutting.

[0159] (2) Preparation of negative electrode sheet:

[0160] (2.1) Preparation of support layer 10:

[0161] The polymer material and the two-dimensional nanobelt material were melt-blended at 220° C., uniformly dispersed at a rotation speed of 1000 rpm for 4 hours, and formed into a support layer 10 by a calendering method.

[0162] Wherein, the polymer material is polypropylene (PP);

[0163] The 2D nanobelt material is NbAs, with a thickness of 250 nm, a width of 400 nm, and a length of 0.5 mm;

[0164] The mass ratio of polymer material to two-dimensional nanobelt material is 100:12;

[0165] The thickness of the support layer 10 is 4.5 μm.

[0166] (2.2) Preparation of safety coating 20: Same as step (1.2).

[0167] (2.3) Preparation of protective coating 30: Same as step (1.3).

[0168] (2.4) Preparing the conductive layer 40:

[0169] The reaction chamber was evacuated to 5 × 10 -5 Pa, argon gas is introduced at a flow rate of 60 sccm, a conductive metal material is used as a sputtering target, and DC magnetron sputtering coating is performed under the conditions of a sputtering gas pressure of 1.5 Pa and a sputtering power of 180 W to form a conductive layer 40 on the protective coating 30.

[0170] The conductive metal material is Cu, and the thickness of the conductive layer 40 is 1 μm.

[0171] (2.5) Preparation of negative electrode sheet:

[0172] The negative electrode active material graphite (Gr), the binder CMC and SBR, and the conductive agent SP are dispersed in a solvent deionized water according to a mass ratio of 80:4:6:10, and the negative electrode slurry is obtained after homogenization; the negative electrode slurry is coated on the conductive layer 40 of the composite current collector N1, and the negative electrode sheet is obtained after drying, rolling and cutting.

[0173] (3) Assembling secondary batteries:

[0174] In a glove box (Ar atmosphere, water, O 2 The positive electrode, glass fiber separator and negative electrode are encapsulated with aluminum plastic film, and the electrolyte is injected to form a laminated soft-pack battery cell; wherein the electrolyte includes 1 mol / L LiPF 6 and organic solvents (EC and EMC in a 1:1 volume ratio).

[0175] Embodiments 2 to 8

[0176] Embodiments 2 to 8 are substantially the same as Embodiment 1, except that:

[0177] Example 2: The mass ratio of the polymer material to the two-dimensional nanobelt material is 100:5;

[0178] Example 3: The mass ratio of the polymer material to the two-dimensional nanobelt material is 100:20;

[0179] Example 4: The two-dimensional nanobelt material is replaced with TaAs of equal mass, with a thickness of 280 nm, a width of 350 nm, and a length of 0.5 mm;

[0180] Example 5: The two-dimensional nanobelt material is replaced with an equal mass of NbP, with a thickness of 260 nm, a width of 380 nm, and a length of 0.5 mm;

[0181] Example 6: The mass ratio of the binder to the inorganic foaming agent is 1:2;

[0182] Example 7: The inorganic foaming agent is replaced with an equal mass of beryllium carbonate (BeCO 3 ).

[0183] Embodiment 8: No grooves 11 are formed on the surface of the support layer 10, and a safety coating 20 with a thickness of 1 μm is formed on the surface of the support layer 10 by using the mixed liquid by a scraping method.

[0184] Comparative Examples 1 to 8

[0185] Comparative Examples 1 to 8 are substantially the same as Example 8, except that:

[0186] Comparative Example 1: No two-dimensional nanomaterials are added to the support layer, and no safety coating and protective coating are provided;

[0187] Comparative Example 2: No two-dimensional nanomaterial is added to the support layer;

[0188] Comparative Example 3: The two-dimensional nanomaterial is replaced with silicon dioxide with a particle size of 300 nm;

[0189] Comparative Example 4: No safety coating and protective coating are provided;

[0190] Comparative Example 5: No safety coating is provided;

[0191] Comparative Example 6: The inorganic foaming agent in the safety coating is replaced with basic copper carbonate, and the thermal decomposition temperature is about 200°C;

[0192] Comparative Example 7: No protective coating is provided;

[0193] Comparative Example 8: The material of the positive electrode protective coating is replaced by Al, and the material of the negative electrode protective coating is replaced by Ni.

[0194] Test Case

[0195] The following tests were performed on each embodiment and each comparative example:

[0196] (1) Mechanical strength of the composite current collector: Cut three sample strips with a length and width of 150 mm × 15 mm, ensure that the samples are placed vertically on the test clamp of the tensile testing machine, set the test parameters and start the test, and record the tensile strength.

[0197] (2) Peel strength of composite current collector: Attach the tape flatly to the steel plate, fix the sample on the tape, attach the auxiliary tape to the surface of the sample, fix the steel plate and the auxiliary tape on a constant speed tensile machine to start the test, and record the peel strength of each sample.

[0198] (3) Lithium-to-Drag Ratio of the Battery: After the battery is fully charged, its internal resistance values ​​R1 and R2 are tested at 25°C and 130°C respectively, and the Lithium-to-Drag Ratio of the battery is calculated based on R2 / R1.

[0199] (4) Room temperature cycle test: The battery is subjected to a room temperature cycle test at 2C / 2C, and the battery's first discharge specific capacity at 2C and the number of cycles at which the capacity decays to 80% are recorded.

[0200] The above test results are shown in Table 3.

[0201] It can be seen from Table 3 that for Examples 1 to 8, the tensile strength of the composite current collector P in the positive electrode sheet is 188MPa~196MPa, the peel strength is 4.4N / 25mm~4.8N / 25mm, and the tensile strength of the composite current collector N in the negative electrode sheet is 202MPa~210MPa, and the peel strength is 5.2N / 25mm~5.5N / 25mm, which has the advantages of high tensile strength and high peel strength. After being assembled into a battery, the rise-to-resistance ratio from 25°C to 130°C is 14.3~26.5, which proves that the internal resistance of the battery cell at high temperature is significantly increased, and the abnormal loop current can be suppressed, effectively reducing the probability of thermal runaway of the battery at high temperature. The first discharge specific capacity of the battery at 2C is 184.2mAh / g~185.3mAh / g, and the number of cycles for the capacity to decay to 80% is 743~863 times, which has the advantages of high specific capacity and good cycle performance.

[0202] Compared with Example 1, Example 2 reduces the amount of two-dimensional nanobelt material, and Example 3 increases the amount of two-dimensional nanobelt material, resulting in a slight deterioration in the mechanical properties of the composite current collector, and a decrease in the lift-to-drag ratio of the battery, a decrease in the first discharge specific capacity at 2C, and a slight decrease in the number of cycles, proving that the addition of a suitable amount of two-dimensional nanobelt material has a certain improvement effect on the mechanical properties of the composite current collector and the capacity, cycle performance and safety performance of the battery. Example 4 uses TaAs nanobelts, and Example 5 uses NbP nanobelts, resulting in a significant decrease in the number of battery cycles, because the electronic conductivity of TaAs and NbP two-dimensional nanobelts is not as good as NbAs, which leads to an increase in the resistance of the composite current collector, and significant heat generation during the cycle at a 2C rate, resulting in a deterioration in the cycle performance. The amount of inorganic foaming agent used in Example 6 is reduced, resulting in a significant decrease in the lift-to-drag ratio of the battery, proving that an increase in the amount of inorganic foaming agent is beneficial to reducing the probability of thermal runaway at high temperatures, thereby improving the safety performance of the battery. In Example 7, beryllium carbonate is used as the inorganic foaming agent, and the lift-to-drag ratio is reduced, which proves that using sodium silicate decahydrate as the inorganic foaming agent can obtain better safety performance.

[0203] The composite current collector P and composite current collector N of Example 8 are not provided with grooves, the peel strength of the current collector becomes lower, and the lift-to-drag ratio of the battery cell under high temperature conditions becomes smaller, which in turn affects the cycle performance and safety performance of the battery cell. This proves that the design of the groove structure helps to increase the contact area, improve the surface roughness, and enhance the bonding force between layers, thereby improving the cycle stability of the battery cell; the foaming material layer is applied in the groove structure, and after the battery cell is abnormally heated to the thermal decomposition temperature, the inorganic foaming agent will form a greater impact force in the limited groove space, which will destroy the conductive layer and the electrode material layer on its surface, increase the impedance of the battery cell (increase the lift-to-drag ratio of the battery cell), and limit the abnormal current.

[0204] Compared with Example 8, the support layer in Comparative Example 1 does not add two-dimensional nanofillers, nor does it have a safety coating and a protective coating, which results in a significant decrease in the tensile strength, peel strength of the composite current collector, and the lift-to-drag ratio and cycle performance of the battery. The support layer in Comparative Example 2 does not add two-dimensional nanofillers, but has a safety coating and a protective coating. Although the lift-to-drag ratio of the battery is significantly improved, the tensile strength, peel strength and cycle performance of the composite current collector are still relatively poor. The support layer in Comparative Example 3 adds SiO 2Nanoparticles, the tensile strength, peel strength and battery cycle performance of the composite current collector are improved compared with Comparative Example 2, but there is still a significant gap with Example 1. This proves that the two-dimensional nanobelt material helps to improve the mechanical properties of the support layer, enhance the tensile strength and peel strength of the composite current collector, and the improvement effect of the two-dimensional nanobelt material is more significant than that of nanoparticles; in addition, the excellent conductivity of the nano two-dimensional belt material can reduce the resistance of the composite current collector itself, avoid overcurrent heating during the high current charging and discharging process of the battery, and thus improve the electrochemical stability of the battery.

[0205] Compared with Example 8, Comparative Example 4 does not have a safety coating and a protective coating, and its peel strength is reduced, and the lift-to-drag ratio and cycle performance of the battery are significantly deteriorated. Comparative Example 5 does not have a safety coating, and its peel strength and cycle performance are improved compared with Comparative Example 4, but the lift-to-drag ratio is still very poor. Comparative Example 6 uses basic copper carbonate as an inorganic foaming agent, and its thermal decomposition temperature is about 200°C, resulting in a lift-to-drag ratio of only 1.32 when the battery is heated from 25°C to 130°C. This proves that the use of a suitable inorganic foaming agent can ensure a lower probability of thermal runaway at high temperatures.

[0206] Compared with Example 8, Comparative Example 7 does not have a protective coating, and Comparative Example 8 uses a single metal to make the protective coating. The cycle performance of the battery deteriorates, which proves that using high entropy alloy material as a protective coating can not only protect the foaming material, but also increase the adhesion of the conductive layer, thereby improving the cycle performance of the battery.

[0207] In summary, the composite current collector designed in this application integrates excellent mechanical properties and electrical conductivity, which helps to ensure the cycle stability of the battery cell under 2C rate charge and discharge conditions. When the temperature inside the battery cell rises abnormally to 80℃~130℃, the inorganic foaming material will undergo an endothermic decomposition reaction, releasing a large amount of CO 2 , H 2 O and other non-flammable and non-combustible gases, and destroy the conductive layer on the surface, improving the safety performance of the battery cell from multiple dimensions.

[0208] Table 1. Composite current collector P in the positive electrode sheet

[0209]

[0210] Note 1: The mass ratio A refers to the mass ratio of the polymer material and the two-dimensional nanobelt material, the mass ratio B refers to the mass ratio of the binder and the inorganic foaming agent, the thickness of the support layer is 6μm, the thickness of the safety coating is 1.5µm, the thickness of the protective coating is 30nm, and the thickness of the conductive layer is 1µm.

[0211] Table 2. Composite current collector N in the negative electrode sheet

[0212]

[0213] Note 2: The mass ratio A refers to the mass ratio of the polymer material and the two-dimensional nanobelt material, the mass ratio B refers to the mass ratio of the binder and the inorganic foaming agent, the thickness of the support layer is 4.5μm, the thickness of the safety coating is 1.5µm, the thickness of the protective coating is 30nm, and the thickness of the conductive layer is 1µm.

[0214] Table 3. Composite current collector and battery performance

[0215]

[0216] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0217] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of protection of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the scope of protection of the present application. Therefore, the scope of protection of the present application shall be subject to the attached claims.

Claims

1. A composite current collector, characterized in that: It includes a supporting layer, a safety coating, a protective coating and a conductive layer stacked in sequence; The support layer includes a polymer material and a two-dimensional nanobelt material; The safety coating comprises a binder and an inorganic foaming agent, and the thermal decomposition temperature of the inorganic foaming agent is 80° C. to 130° C.; The protective coating includes a high entropy alloy material.

2. The composite current collector according to claim 1, characterized in that: The surface of the support layer is provided with a plurality of grooves, and the depth of the grooves is less than the thickness of the safety coating; The safety coating is filled in the groove; The protective coating covers the safety coating and the supporting layer.

3. The composite current collector according to claim 2, characterized in that: The depth of the groove is 0.1 μm to 1 μm, the size of the groove is 1 μm to 2 μm, and the spacing between the grooves is 200 μm to 1000 μm.

4. The composite current collector according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The polymer material includes one or more of polyethylene, polypropylene, polyimide, polyvinyl chloride, polystyrene, polyvinyl alcohol, polyethylene terephthalate and polybutylene terephthalate; (2) The two-dimensional nanoribbon material comprises one or more of tantalum arsenide nanoribbon, niobium arsenide nanoribbon, tantalum phosphide nanoribbon and niobium phosphide nanoribbon; (3) The two-dimensional nanobelt material has a thickness of 50 nm to 400 nm, a width of 100 nm to 500 nm, and a length of 0.1 mm to 1 mm; (4) The mass ratio of the polymer material to the two-dimensional nanobelt material is 100:(1-30); (5) The thickness of the support layer is 4 μm to 8 μm.

5. The composite current collector according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium alginate, polyvinyl alcohol, polymethyl methacrylate, hydrogenated nitrile rubber and polyacrylic acid; (2) The inorganic foaming agent includes one or more of carbonates, bicarbonates and hydrated silicates; (3) The mass ratio of the binder to the inorganic foaming agent is 1:(2-3); (4) The thickness of the safety coating is 0.2 μm to 2 μm.

6. The composite current collector according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The high entropy alloy material includes at least five of iron, cobalt, nickel, chromium, manganese, aluminum, copper, titanium, yttrium and tantalum; (2) The thickness of the protective coating is 20nm~50nm.

7. The composite current collector according to any one of claims 1 to 3, characterized in that: One or more of the following conditions are met: (1) The material of the conductive layer includes one or more of stainless steel, copper, nickel and aluminum; (2) The thickness of the conductive layer is 0.5 μm to 4 μm.

8. A method for preparing a composite current collector according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polymer material and the two-dimensional nanobelt material are melt-blended and molded to form a support layer; A safety coating layer, a protective coating layer and a conductive layer are sequentially formed on the support layer.

9. The method for preparing a composite current collector according to claim 8, characterized in that: The preparation method of the safety coating comprises the following steps: Covering the support layer with a mixed slurry containing a binder and an inorganic foaming agent, and drying the mixed slurry to obtain the safety coating; or, The surface of the support layer includes a first area and a second area arranged around the first area; forming a plurality of grooves on the first region and covering the second region with a mask; The groove is filled with a mixed slurry containing a binder and an inorganic foaming agent, and then dried, and the mask is removed to obtain the safety coating.

10. A secondary battery, characterized in that: The composite current collector comprises the composite current collector as claimed in any one of claims 1 to 7, or comprises the composite current collector prepared by the method for preparing the composite current collector as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Superconducting current collector and preparation method thereof

    CN115588747A

  • Metal copper composite current collector, preparation method thereof, electrode plate and battery

    CN116454286A

  • Composite current collector and preparation method thereof, electrode and energy storage device

    CN117996089A

  • Corrosion-resistant composite current collector and preparation method thereof

    CN118263447A

  • Current collector, pole piece, secondary battery, battery module, battery pack, and electric device

    CN118476066A

Cited By

  • Conductive composite current collector, preparation method thereof and battery

    CN119581570A